Subconjunto terminológico da CIPE® para atendimento de pessoas com hanseníase - Oliveira, Michele Dias da Silva (2017)
Introduction: To take care of people with leprosy, nurses make diagnostic and therapeutic judgments, which must be expressed through special terminology of the profession of theoretical nursing models. Therefore, the International Classification for Nursing Practice usage - CIPE® for the construction of a terminological subset aimed at people with leprosy is necessary to train nurse clinical practice. Objective: To create a terminological subset of nursing diagnoses, results and interventions for the care of people with leprosy, using CIPE® in clinical practice. Method: This is a methodological research study with two phases: one exploratory and the other, a field study. In the exploratory phase, three stages were used to perform terminological research and cross mapping between the terms extracted from Health Ministry publications, related to leprosy and those contained in CIPE® version 2015. In field phase: 1 - Nursing consultation based on Orem's self-care theory with elaboration of nursing diagnosis, results and interventions; 2 - Nursing diagnosis statements validation by three specialists; 3 - Cross mapping of diagnostic statements, results and nursing interventions with CIPE® and the database of terms extracted from the Health Ministry publications; 4 - Creation of the terminology subset of CIPE® to assist people with leprosy. Results: In exploratory phase, 1,041 terms were extracted from the Ministry of Health publications related to leprosy, from which 300 (28.80%) were equal to constant terms in the CIPE® axes; 51 (4.86%) were similar; 49 (4.68%) were larger; 172 (16.45%) were more restricted and 469 (45.00%) were different from the terms of that classification. In field phase, nursing consultations have been carried out on 24 people with leprosy, resulting in 81 nursing diagnoses / results and 303 nursing interventions. In the statements analysis of diagnosis / results and nursing interventions, 564 primitive terms have been evaluated: 342 (61%) were considered constant (equal term, similar, similar more restricted and Similar) in CIPE® and 222 (39.4%) different from CIPE®. From pre-coordinated terms, 384 were evaluated, from which 275 (72%) were considered constant (equal term, similar, more similar, similar and broader) and 109 (28.4%) different from pre-coordinated ICNP terms. Conclusions: The methodology used in this research made it possible to create a terminological subset based on Dorothea Orem self-care theory and CIPE®, and it can be used in clinical practice in nursing care to people with leprosy, in a systematized way, using the steps of nursing process and assisting in the teaching and creation of electronic medical records. In addition, from the results found in this study, it was noticed the need to expand CIPE® in order to better contemplate the phenomena of nursing practice in the care of people with leprosy.